THE IMPACT OF COMPLEMENTARY FOOD INTERVENTIONS ON CHILDHOOD STUNTING PREVENTION: A SYSTEMATIC REVIEW - Grathima, Eishca Fanani; Yunitasari, Esti; Indarwati , Retno (Indonesian Journal of Community Health Nursing, 2024)
Introduction: The transition from exclusive breastfeeding to poor complementary food by feeding practices may put infants at higher risk of becoming stunting. This study aims to analyze complementary food interventions in early childhood for stunting prevention.   Method: This systematic review is using 16 journals, and the authors conducted a relevant literature review in various data using the keywords “complementary food, stunting, RCT”. Data based on SCOPUS, Ebsco, WOS and Pubmed. The criteria consisted of full text published in criteria were five years limit journal (2017-2022) use article using English and live in lower middle income countries.   Results: In the first 1000 days of beginnings complementary food interventions are effective in preventing stunting. The incorporation of behavior change communication (BCC) education into the care programs offered to mothers and their families should be considered as a methods for gaining the most advantageous results.   Conclusion: There are many options for complementary foods in the first 1000 days of life and can be adapted to the characteristics of the place of residence. The combination of behavior change communication (BC) interventions provided by medical personnel in the community to mothers and families who are directly involved in childcare can optimize stunting prevention interventions. Keywords: stunting prevention intervention, complementary food